Magnetic breakdown in the semimetallic InAs/GaSb system - Symons, D; Lakrimi, M; Nicholas, R; Maude, D; Portal, J; Mason, N; Walker, P (1998)
We have performed tilted field magnetotransport measurements of semimetallic InAs/GaSb structures. It has been observed that superlattices behave in a distinctly different manner to single quantum well samples. We show that the observation of Shubnikov-de-Haas (SdH) oscillations requires that carriers are able to tunnel across the gaps between the unconnected Fermi surface islands. (C) 1998 Elsevier Science B.V. All rights reserved.